STATISTICAL EVALUATION OF FATIGUE DATA OF COMPONENTS - Chi Nghia Chung; Zoltan Major (Acta Polytechnica CTU Proceedings, 2016)
A variety of steels, cast iron grades and other metals have long been used for the production of machine components. In recent years, however, new materials such as sintered materials and plastics become increasingly important. Because of the large number of different fibers, matrices, stacking sequences, processing conditions and processes and the variety of resulting material configurations it is not possible to rely on proven fatigue models for conventional materials. Moreover, the development of models, which are valid for all composites are generally extremely difficult. In this work, a possible application of high-performance composites as materials for machine elements are investigated. This study attempts to predict the fatigue behavior and the consequent durability, based on laboratory measurements. Using the statistics program JMP, the aquired data was subjected to a reliability analysis in order to ensure the plausibility, validity and accuracy of the measured values.